EFFECTS OF ECONOMIC CRISIS ON MIGRATION – EVIDENCE FROM ALBANIA - Grabova, Perseta; Dosti, Bernard; Pojani, Elona (European Scientific Journal, ESJ, 2013)
﻿﻿Based on a survey which was conducted during January 2012, this study, aims to find out the main consequences of the current economic crisis on Albanian households and the effect they have had on migration decision. The target groups of the analysis are young students, who are considering the possibility of studying abroad and students/professionals who are currently studying/working abroad or who have studied/worked abroad and now have returned to Albania. The content of the survey addresses issues related to income level, family background, employment possibilities, level of salaries, working conditions, social environment, and public policies. The conclusions of the study are that the most important effects of the economic crisis are the reduction of the rewards from work and the decline of quality of life. As the effects of the crises affect the migration decision of Albania and thus the future patterns of migration, identifying push and pull factors of migration is crucial for future macroeconomic and social stability.